ANGGARAN FLEKSIBEL BERDASARKAN AKTIFITAS SEBAGAI ALAT BANTU DALAM PERENCANAAN DAN PENGENDALIAN BIAYA - Santiyasari, Anita Septi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to give description of usage/advantage of flexible budget in the potential planning and cost controlling production. One of the phenomena occurs at PT Pertani Persero UPB Jombang. PT Pertani Persero UPB Jombang has implemented conventional approach in statics budget in which the statics budget depends on the determined capacity level. Statics budget is not quite useful in the preparation of performance report. A solution is required in order to fix the performance report by using activity based flexible budget. Activity based flexible budget is a kind of budgeting which is designed to create some cost levels in the range which can be compared to the cost which actually occurs.Keywords: static budget, flexible budget, activity, production cost, planning and controlling.